DEVELOPING AND SELECTING SLOPE STABILIZATION TECHNIQUES IN MANAGING SLOPE FAILURES - Sandyavitri, Ari (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2014)
This paper objectives are to; (i) identification of risky slopes (within 4 Provinces in Sumatra including Provinces of Riau, West Sumatra, Jambi and South Sumatra encompassing 840 kms of the â€œJalan Lintas Sumatraâ€ highway) based on Rockfall Hazard Rating Systems (RHRS) method; (ii) developing alternatives to stabilize slope hazards, and (iii) selecting appropriate slopes stabilization techniques based on both proactive approach and value engineering one. Based on the Rockfall Hazard Rating Systems (RHRS) method, it was identified 109 steep slopes prone to failure within this highway section. Approximately, 15 slopes were identified as potential high-risk slopes (RHRS scores were calculated >200 points). Based on the proactive approach, seven riskiest slopes ware identified. The preferred stabilization alternatives to remedy most of these slopes are suggested as follow; either (i) a combination of retaining wall and drainage, or (ii) gabion structure and drainage. However, different approaches may yield different results, there are at least 2 main consideration in prioritizing slope stabilization; (i) based on the riskiest slopes, and(ii) the least expensive stabilization alternatives.